A method for preparing a lithium-ion battery separator, a separator prepared therefrom, and applications thereof

By using electrocatalytic etherification reaction and electrospinning technology in lithium-ion battery separators, high thermal stability and high wettability separators were prepared, which solved the shortcomings of existing separators in porosity and wettability, and improved the Performance and safety of lithium-ion batteries.

CN118920018BActive Publication Date: 2025-01-17DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411416630.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-17
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

Existing lithium-ion battery separators have shortcomings in low porosity and low wettability, resulting in limited battery resistance, energy density and magnification capabilities, and short circuits of materials melt and shrink at high temperatures.

Method used

By adding a phase transfer catalyst to an aqueous solution of ultra-high polymerization polymer and mixing it with acrylonitrile, electrocatalytic etherification reaction, precipitation, filtration, and drying, and then preparing a lithium-ion battery separator through electrospinning technology to adjust the material ratio and process conditions to improve thermal stability and wettability of the diaphragm.

Benefits of technology

The preparation of high thermal stability, high mechanical strength and high wettability separators is achieved, which improves the electrochemical performance and cycle life of lithium-ion batteries, avoids dendrite growth and battery short circuits, and enhances the application potential of the separator.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118920018B_ABST
    Figure CN118920018B_ABST
Patent Text Reader

Abstract

The present application discloses a method for preparing a lithium-ion battery separator and the separator and application thereof, belonging to the field of battery materials. The method comprises the following steps: adding a phase transfer catalyst to an aqueous solution containing a polymer with an ultra-high degree of polymerization for reaction, then mixing with acrylonitrile to obtain a mixed system, performing an electrocatalytic etherification reaction under the catalytic conditions of a platinum-palladium catalytic electrode, precipitating, filtering, drying, dissolving, spinning, and obtaining the lithium-ion battery separator. The prepared separator has extremely strong electrolyte wettability, and the separator prepared by the electrostatic spinning process has an excellent pore structure, improves the transmission speed and migration number of lithium ions, induces uniform deposition of lithium ions, effectively inhibits dendrite growth, improves battery rate discharge performance and high rate cycle performance, improves the electrochemical performance and cycle life of lithium-ion batteries, and the separator has huge application potential in the field of lithium-ion battery separators.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to a method for preparing a lithium-ion battery separator, the prepared separator, and its application, belonging to the field of battery materials. Background Art

[0002] Currently, most commercially available lithium-ion battery separators focus on polyolefin membranes such as polyethylene (PE) and polypropylene (PP), which possess good chemical stability and high mechanical strength. However, the low porosity and poor wettability of polyolefin membranes with polar liquid electrolytes severely affect battery resistance, energy density, and rate capability. Polyolefin materials can also melt and shrink at high temperatures, causing short circuits. An ideal separator should possess low interfacial resistance, high electrolyte wettability, and uniform pore distribution to meet the requirements for normal battery operation in various applications. Separators need to possess high thermal stability, high mechanical strength, and high wettability to meet these requirements. Therefore, adjusting raw material ratios and copolymerizing different polymers to prepare separators is crucial for the development of lithium-ion batteries. Developing separators with high thermal stability, high mechanical strength, and high wettability to replace traditional commercial separators and further improve the performance and safety of lithium-ion batteries is of paramount importance.

[0003] Electrospinning technology enables the continuous production of micron-sized nanofiber membranes. Nanofiber membranes possess a large specific surface area, high porosity, small pore size, and strong adsorption capacity, which can improve the wettability and thermal stability of separators. Furthermore, with the development and commercialization of large-scale electrospinning equipment, mass production of nanofibers has become possible. For example, patent CN105428572A uses electrospinning to prepare lithium-ion battery separators; patent CN110565269A uses coaxial electrospinning to prepare lithium battery separators. Summary of the Invention

[0004] According to one aspect of this application, a method for preparing a lithium-ion battery separator is provided, comprising the following steps:

[0005] A phase transfer catalyst is added to an aqueous solution containing a polymer with ultra-high polymerization degree and reacted. The mixture is then mixed with acrylonitrile to obtain a mixed system, which is then subjected to an electrocatalytic etherification reaction. After precipitation, filtration, drying, dissolution, and spinning, the lithium-ion battery separator is obtained.

[0006] The thickness of the lithium-ion battery separator is 12~45µm.

[0007] Optionally, the thickness of the lithium-ion battery separator is any value or a range between 12µm, 15µm, 20µm, 25µm, 30µm, 35µm, 40µm, and 45µm.

[0008] The ultra-high degree of polymerization polymer is selected from at least one of vinyl acetate-ethylene copolymer (EVA), polyvinyl acetate (PVAC), and vinyl acetate-vinyl chloride copolymer (EVC).

[0009] The degree of polymerization of the ultra-high degree polymer is 1800~2500.

[0010] Optionally, the degree of polymerization of the ultra-high degree polymer is any value among 1800, 1900, 2000, 2100, 2200, 2300, 2400, and 2500, or a range between any two.

[0011] In the mixed system, the mass fraction of each component is:

[0012] Polymers with ultra-high degree of polymerization: 25~35wt%; optionally, any value from 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, 31wt%, 32wt%, 33wt%, 34wt%, 35wt% or any range between both.

[0013] Water: 25~47wt%; optionally, any value from 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 47wt% or any range between two.

[0014] Phase transfer catalyst: 2~5 wt%; optionally, any value from 2 wt%, 3 wt%, 4 wt%, 5 wt% or any range between two.

[0015] Acrylonitrile: 25~35wt%. Optionally, it is any value from 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, 31wt%, 32wt%, 33wt%, 34wt%, 35wt%, or any range between two.

[0016] The phase transfer catalyst is a quaternary ammonium salt, selected from one of tetrabutylammonium bromide, benzyltriethylammonium bromide, and dodecyltrimethylammonium chloride.

[0017] The reaction temperature is 30~60℃.

[0018] Optionally, the temperature of the reaction is any value of 30°C, 40°C, 50°C, 60°C, or a range between any two.

[0019] The stirring rate for the reaction is 400-800 rpm.

[0020] Optionally, the stirring rate of the reaction is any value among 400 rpm, 500 rpm, 600 rpm, 700 rpm, and 800 rpm, or a range between any two.

[0021] The reaction time is 1 to 3 hours.

[0022] Optionally, the reaction time is any value among 1h, 2h, and 3h, or a range between any two.

[0023] The mixing temperature is 30~60℃.

[0024] Optionally, the mixing temperature is any value among 30°C, 40°C, 50°C, and 60°C, or a range between any two.

[0025] The mixing speed is 400~800 rpm.

[0026] Optionally, the mixing speed is any value among 400 rpm, 500 rpm, 600 rpm, 700 rpm, and 800 rpm, or a range between any two.

[0027] The mixing time is 1 to 3 hours.

[0028] Optionally, the mixing time is any value among 1h, 2h, and 3h, or a range between any two.

[0029] The electrocatalytic etherification reaction is carried out at a temperature of 25-30°C.

[0030] Optionally, the temperature of the electrocatalytic etherification reaction is any value among 25°C, 26°C, 27°C, 28°C, 29°C, and 30°C, or a range between any two.

[0031] The current density of the electrocatalytic etherification reaction is 30~60 mA·cm. -2 .

[0032] Optionally, the current density of the electrocatalytic etherification reaction is 30 mA·cm⁻¹. -2 40mA·cm -2 50mA·cm -2 60mA·cm -2 Any value in the range or any value between the two.

[0033] The electrocatalytic etherification reaction takes 1-2 hours.

[0034] Optionally, the time for the electrocatalytic etherification reaction is any value among 1 h, 1.5 h, and 2 h, or any range between two of them.

[0035] The electrocatalytic etherification reaction was carried out under platinum-palladium catalytic electrode conditions.

[0036] Optionally, the preparation method includes the following steps:

[0037] 1) Place the ultra-high degree polymer and solvent into a four-necked flask equipped with a thermometer, stirrer, reflux condenser and dropping funnel and place it in a constant temperature water bath. Heat and stir until homogeneous. The conditions are: 35~65℃, rotation speed 400~800 rpm, time 3~6h.

[0038] 2) Allow the mixture to cool naturally to room temperature, add the phase transfer catalyst, and heat and stir the reaction.

[0039] 3) Add acrylonitrile and mix;

[0040] 4) The entire reaction system is transferred to an electrocatalytic device for electrocatalytic etherification under platinum-palladium catalytic electrode conditions;

[0041] 5) Add deionized water, precipitate, filter, and dry to obtain the product.

[0042] According to another aspect of this application, a lithium-ion battery separator is provided, which is prepared by the above-described preparation method.

[0043] The solvent used for dissolution is selected from at least one of DMAC, DMF, and DMSO.

[0044] The mass fraction of the dissolved spinning solution is 9~18wt%.

[0045] Optionally, the mass fraction of the dissolved spinning solution is any value or a range between 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, and 18wt%.

[0046] The spinning process is electrospinning.

[0047] According to another aspect of this application, an application of the above-described lithium-ion battery separator is provided for use in a lithium-ion battery.

[0048] The beneficial effects that this application can produce include:

[0049] 1) This application uses an electrocatalytic device to replace the traditional alkaline catalytic system for the cyanoethylation reaction of polymers, which is safe and environmentally friendly, avoids environmental pollution, and has extremely high electrocatalytic efficiency, which greatly reduces the self-polymerization of acrylonitrile and reduces the amount of acrylonitrile used.

[0050] 2) The modified ultra-high degree polymer contains strong polar cyano groups, and the prepared separator has extremely strong electrolyte wettability. The separator prepared by electrospinning process has excellent pore structure, which improves the lithium ion transport speed and transport number, induces uniform lithium ion deposition, effectively inhibits dendrite growth, improves the battery rate discharge performance and high rate cycle performance, and improves the electrochemical performance and cycle life of lithium-ion batteries. The separator has great application potential in the field of lithium-ion battery separators.

[0051] 3) Modified polymers with ultra-high degree of polymerization have ultra-high dielectric constants and can be used for electrospinning to make membranes. The membranes prepared have excellent performance in lithium-ion batteries. They can improve the wettability of the membrane to the electrolyte, improve the mechanical strength of the membrane, enhance stability, and prevent short circuits caused by dendrite puncture. They are expected to provide a reference for solving the shortcomings of existing materials and designing and developing high-performance materials. Attached Figure Description

[0052] Figure 1 These are the long cycle curves of lithium iron phosphate full cells assembled with separators in the embodiments and comparative examples of this application at 1C. Detailed Implementation

[0053] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0054] Unless otherwise specified, the raw materials and catalysts used in the embodiments of this application were all purchased commercially.

[0055] Example 1

[0056] 1) Place 30g of polyvinyl acetate with a degree of polymerization of 1800 and 35g of water into a four-necked flask equipped with a thermometer, stirrer, reflux condenser and dropping funnel and place it in a constant temperature water bath. Heat to 45℃ and stir at 600 rpm for 3 hours until homogeneous.

[0057] 2) Allow the mixture to cool naturally to room temperature, add 3g of the phase transfer catalyst tetrabutylammonium bromide, heat to 35℃, and react at 500 rpm for 2 hours;

[0058] 3) Add 32g of acrylonitrile and continue stirring and mixing at 35℃ and 500 rpm for 2 hours;

[0059] 4) Transfer the entire reaction system to the electrocatalytic device and set it at 25°C with a current density of 60 mA·cm⁻¹. -2 And the electrocatalytic etherification reaction was carried out for 1 hour under platinum-palladium catalytic electrode conditions;

[0060] 5) Add deionized water, precipitate, filter, and dry to obtain the product.

[0061] The polymer obtained above was dissolved in DMF, and the spinning solution had a mass fraction of 15 wt%. Spinning was performed to obtain an electrospun film with a thickness of 22 μm.

[0062] Example 2

[0063] 1) Place 25g of vinyl acetate-ethylene copolymer with a degree of polymerization of 2500 and 47g of water into a four-necked flask equipped with a thermometer, stirrer, reflux condenser and dropping funnel and place it in a constant temperature water bath. Heat to 35℃ and stir at 800 rpm for 5 hours until homogeneous.

[0064] 2) Allow the mixture to cool naturally to room temperature, add 2g of the phase transfer catalyst benzyltriethylammonium bromide, heat to 60℃, and react at 400 rpm for 1 hour;

[0065] 3) Add 26g of acrylonitrile and continue mixing at 60℃ and 400 rpm for 1 hour;

[0066] 4) Transfer the entire reaction system to the electrocatalytic device and set it at 30°C with a current density of 30 mA·cm⁻¹. -2 And the electrocatalytic etherification reaction was carried out for 2 hours under platinum-palladium catalytic electrode conditions;

[0067] 5) Add deionized water, precipitate, filter, and dry to obtain the product.

[0068] The polymer obtained above was dissolved in DMAC, and the spinning solution had a mass fraction of 18 wt%. Spinning was performed to obtain an electrospun film with a thickness of 12 μm.

[0069] Example 3

[0070] 1) Place 35g of vinyl acetate-vinyl chloride copolymer with a degree of polymerization of 2000 and 25g of water into a four-necked flask equipped with a thermometer, stirrer, reflux condenser and dropping funnel and place it in a constant temperature water bath. Heat to 65℃ and stir at 400 rpm for 6 hours until homogeneous.

[0071] 2) Allow the mixture to cool naturally to room temperature, add 5g of phase transfer catalyst dodecyltrimethylammonium chloride, heat to 30℃, and react at 800 rpm for 1 hour;

[0072] 3) Add 35g of acrylonitrile and continue mixing at 30℃ and 800 rpm for 3 hours;

[0073] 4) Transfer the entire reaction system to the electrocatalytic device and set it at 30°C with a current density of 40 mA·cm⁻¹. -2 And the electrocatalytic etherification reaction was carried out for 2 hours under platinum-palladium catalytic electrode conditions;

[0074] 5) Add deionized water, precipitate, filter, and dry to obtain the product.

[0075] The polymer obtained above was dissolved in DMSO, and the spinning solution had a mass fraction of 9 wt%. Spinning was performed to obtain an electrospun film with a thickness of 45 μm.

[0076] Comparative Example 1

[0077] Comparative Example 1 is an electrospun PAN nanofiber membrane with a thickness of 22 μm.

[0078] Test Example 1

[0079] The separators from Example 1 and Comparative Example 1 were cut into 19mm discs, assembled into lithium iron phosphate full cells, and their polarization long-cycle curves at 1C were tested. The results are as follows: Figure 1 As shown. The batteries assembled with separators in Examples 1-3 can cycle stably for 200 hours, while the battery assembled with separator in Comparative Example 1 short-circuited after 150 hours of cycling, and its stability and discharge specific capacity were lower than those of the Examples.

[0080] The above description is merely a few embodiments of this application and is not intended to limit this application in any way. Although this application discloses preferred embodiments as described above, it is not intended to limit this application. Any changes or modifications made by those skilled in the art without departing from the scope of the technical solution of this application using the disclosed technical content are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing a lithium ion battery separator, characterized in that: The following steps are involved: Adding a phase transfer catalyst to an aqueous solution containing a polymer with an ultrahigh degree of polymerization to react, then mixing with acrylonitrile to obtain a mixed system, performing an electrocatalytic etherification reaction, precipitating, filtering, drying, dissolving, and spinning to obtain the lithium-ion battery separator; The thickness of the lithium-ion battery separator is 12-45 μm; The polymer with ultra-high polymerization degree is selected from at least one of vinyl acetate-ethylene copolymer, polyvinyl acetate, and vinyl acetate-vinyl chloride copolymer; In the mixed system, the mass fraction of each component is: Ultra-high degree of polymerization polymer: 25~35wt%; Water: 25~47wt%; Phase transfer catalyst: 2~5wt%; Acrylonitrile: 25~35wt%; The degree of polymerization of the ultra-high degree of polymerization polymer is 1800-2500; The phase transfer catalyst is selected from one of tetrabutylammonium bromide, benzyltriethylammonium bromide and dodecyltrimethylammonium chloride.

2. The preparation method according to claim 1, characterized in that: The reaction temperature is 30-60°C; The stirring rate of the reaction is 400-800 rpm; The reaction time is 1 to 3 hours.

3. The preparation method according to claim 1, characterized in that: The mixing temperature is 30-60°C; The stirring rate of the mixing is 400-800 rpm; The mixing time is 1 to 3 hours.

4. The preparation method according to claim 1, characterized in that: The temperature of the electrocatalytic etherification reaction is 25-30°C; The current density of the electrocatalytic etherification reaction is 30-60 mA cm -2 ; The electrocatalytic etherification reaction time is 1 to 2 hours.

5. The preparation method according to claim 1, characterized in that: The electrocatalytic etherification reaction is carried out under the catalytic conditions of platinum-palladium catalytic electrode; The spinning is electrostatic spinning.

6. A lithium ion battery separator, characterized in that: Prepared by the preparation method according to any one of claims 1 to 5.

7. An application of the lithium ion battery separator according to claim 6, characterized in that: Used in lithium-ion batteries.

Citation Information

Patent Citations

  • Preparation method of electrospun composite membrane for lithium ion battery

    CN105428572A

  • Method for preparing lithium battery diaphragm through coaxial electrostatic spinning

    CN110565269A

  • Lithium battery diaphragm as well as preparation method and application thereof

    CN117175141A